Social policy and the reproduction of labour power?: a contemporary dilemma - Wellen, Henrique (Argumentum, 2021)
The different functionalities of social policies carry forward their hegemonic determination, altered by the social struggles and hegemonic interests present in governments and by the structural limits that form the base of relations between the state and the market within the capitalist mode of production. Based on theoretical foundations, this article analyses paradoxes in this dynamic, highlighting the problematic relationship between social policies and the reproduction of the labour power nowadays, which, on the one hand, operates to decrease the cost of maintaining the workers’ life and, on the other, is linked to the intensifying precariousness of work.